Pemanfaatan Resume Medis Sebagai Portofolio Kesehatan Keluarga - Masyfufah, Lilis; Rosyiari, Ahniyatul Ilmiyah; Wahyuni, Titin; Sa’adah, Alfina Asiatus; Faida, Eka Wilda (STIKES Yayasan RS.Dr.Soetomo, 2024)
Indonesia has entered to the digital health transformation era. One of the transformation is the obligation of health care facilities to organize medical record in electronic form. Peduli Lindungi application, which was originally only for Covid-19 tests and vaccines has now expanded is function as a Health Portfolio or Personal Health Record (PHR) in the Satu Sehat application. The Health Portfolio can be compiled based on the Medical Resume obatained from Health services. The use of medical resume for preparing health portfolio has not been widelu used because many people do not understand the function of medical resume. The aim of this activity is to explain the importance of a complete medical resume so that it can be used as material for preparing a family health portfolio. The method is the online seminar method. The result is a medical resume containing the identity and history of the patient’s illness after receiving health services. Medical resume can be used to build family health portfolio. The conclusion is that a family health portfolio needs to be prepared to help manage diseases that may arise in the future.